Sex-Related Differences Include Stage, Histology, and Survival in Urethral Cancer Patients - Wenzel, Mike; Nocera, Luigi; Collà Ruvolo, Claudia; Würnschimmel, Christoph; Tian, Zhe; Shariat, Shahrokh F; Saad, Fred; Briganti, Alberto; Tilki, Derya; Mandel, Philipp; Kluth, Luis A; Chun, Felix K H; et al. (Clinical genitourinary cancer, 2021)
PURPOSE: To test the effect of sex on histologic subtype, stage at presentation, treatment, and cancer-specific mortality (CSM) in urethral cancer. PATIENTS AND METHODS: We identified urethral cancer patients within the Surveillance, Epidemiology, and End Results (SEER) registry (2004-2016). After matching for tumor and patient characteristics, cumulative incidence plots and multivariable competing risks regression models, adjusted for other-cause mortality, tested CSM according to sex. RESULTS: Of 1645 eligible urethral cancer patients, 1073 (65%) were male. Urothelial histologic subtype was most frequent in male (59%) but not female (27%) subjects. Adenocarcinoma, squamous cell carcinoma, and other histologies were more frequent in female patients. Most male subjects harbored T1N0M0 (32%) stage disease, whereas most female subjects harbored T3-4N0M0 (29%) stage disease. In urothelial and adenocarcinoma histologic subtypes, African American female subjects were most prevalent (31 and 78%) versus whites (16 and 52%) versus Hispanics (27 and 74%). In T1N0M0 stage, single-mode surgical treatment was more frequent in male than female patients (respectively, 73% vs 59%). In T3-4 and/or N1-2 stage disease, multimodal therapy was more frequent in female than male (42% vs 37%) patients. In nonmetastatic urethral cancer (T1-4N0-2M0), after propensity score matching for stage, race, treatment, and age, cumulative incidence plots showed 5-year CSM of 36% and 25% in female and male patients, respectively, and after further multivariable adjustment resulted in 1.3-fold higher CSM in female as opposed to male patients (P = .07). CONCLUSION: Female patients with urethral cancer present with higher disease stage. Despite higher rates of multimodal therapy, and despite matching for stage disadvantage, female subjects with urethral cancer exhibited higher CSM.
Keywords: SEER Program; program SEER; mužské pohlaví; běloši; míra přežití; lidé; adenokarcinom; Carcinoma, Squamous Cell; White People; Male; Survival Rate; spinocelulární karcinom; nádory močové trubice; ženské pohlaví; Humans; Urethral Neoplasms; Female; Adenocarcinoma